2012
DOI: 10.1111/j.1600-0404.2012.01656.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of a computational model of vagus nerve stimulation

Abstract: Objectives -The most widely used and studied neurostimulation procedure for medically refractory epilepsy is vagus nerve stimulation (VNS) Therapy. The goal of this study was to develop a computational model for improved understanding of the anatomy and neurophysiology of the vagus nerve as it pertains to the principles of electrical stimulation, aiming to provide clinicians with a systematic and rational understanding of VNS Therapy. Materials and methods -Computational modeling allows the study of electrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
73
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 22 publications
1
73
0
4
Order By: Relevance
“…Furthermore, we are still in need for early clues to refine stimulation parameters without having to wait for changes in body weight. It can be speculated that brain-imaging methods together with computational model of VNS (Helmers et al, 2012) might be of significant help towards this clinical requirement.…”
Section: Invasive Neuromodulation Strategies: Recent Developments Andmentioning
confidence: 99%
“…Furthermore, we are still in need for early clues to refine stimulation parameters without having to wait for changes in body weight. It can be speculated that brain-imaging methods together with computational model of VNS (Helmers et al, 2012) might be of significant help towards this clinical requirement.…”
Section: Invasive Neuromodulation Strategies: Recent Developments Andmentioning
confidence: 99%
“…Consequently, higher stimulation may be required for the activation of the nerve fibers present in the area not covered by the electrode. In contrast, fibers located near the perineurium of a fascicle are exposed to a stronger electric field (Helmers et al, 2012). In addition, the large variation in epineurial connective tissue might influence the effectiveness of VNS (Helmers et al, 2012).…”
Section: Questions-future For Vagus Nerve Stimulation In Inflammatorymentioning
confidence: 99%
“…In contrast, fibers located near the perineurium of a fascicle are exposed to a stronger electric field (Helmers et al, 2012). In addition, the large variation in epineurial connective tissue might influence the effectiveness of VNS (Helmers et al, 2012). Verlinden et al (Verlinden et al, 2016) have shown that the right cervical VN has a 1.5 times larger effective surface area than the left nerve and that there is a broad spreading within the individual nerves.…”
Section: Questions-future For Vagus Nerve Stimulation In Inflammatorymentioning
confidence: 99%
See 2 more Smart Citations